Implementasi Metode Read Aloud Dalam Meningkatkan Minat Membaca Anak Usia 5-6 Tahun Di Ra Annur Prima Kecamatan Medan Labuhan - Layyana Musfirah (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine how the implementation of Read Aloud in increasing interest in reading children aged 5-6 years in RA Annur Prima, Medan Labuhan District and the results of implementing the Read Aloud method in increasing interest in reading children aged 5-6 years in RA Annur Prima, Medan Labuhan District. This research method uses qualitative research with a qualitative descriptive approach. Data collection techniques used in this study were observation, interviews, and documentation. Analysis of the data used is descriptive analysis. The data validity technique uses the triangulation method. Based on the results of research and data analysis, it can be concluded that the implementation of the Read Aloud method can increase the interest in reading children aged 5-6 years in RA Annur Prima, Medan Labuhan District, which is carried out effectively with a duration of 5-10 minutes every day and the results of the implementation of the Read Aloud method many Early childhood who like books, are enthusiastic about reading aloud activities carried out by teachers and there is positive behavior in reading interest in children aged 5-6 years at RA Annur Prima, Medan Labuhan District.